How are cities working in the Spanish territorial development? ( 1985-2000) - José M. Mella (European Regional Science Association (ERSA), 2003)
The economic regional convergence process has attracted much attention through the last decade by regional scientists. This paper tries to deep in this topic, taking into account as a unit of analysis the role that cities have in regional convergence. Sigma and beta convergence are measured following a method based on a production function of the main spanish cities( 124 cities bigger than 50.000 inhabitants.
Keywords: 330